2008
DOI: 10.1021/op800161v
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Soluble Palladium Complexes from Reaction Mixtures by Fixed-Bed Adsorption

Abstract: The increasing use of metal-containing catalysts in producing pharmaceutical intermediates and active pharmaceutical ingredients, in conjunction with requirements of low metal content in a drug substance, has motivated the development of efficient separations processes for metals removal. In this paper, fixed-bed adsorption, an attractive alternative to batch adsorption, was investigated using a reaction mixture from a Heck coupling. Adsorption isotherm determinations using three candidate adsorbents revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The removal of residual catalyst complex from the products of transition metal catalyzed reactions is very important for a number of reasons. [145][146][147][148] First of all there is the chance to recover valuable catalyst complexes, which often contain platinum group metals and sophisticated and thus expensive ligands. 64 Furthermore, especially for use with humans, strict limits for the contamination of chemicals with heavy metals apply, which are in the 1-10 ppm range.…”
Section: Scheme 12 Suzuki Coupling Of Cyclobutyltrifluoroboratesmentioning
confidence: 99%
“…The removal of residual catalyst complex from the products of transition metal catalyzed reactions is very important for a number of reasons. [145][146][147][148] First of all there is the chance to recover valuable catalyst complexes, which often contain platinum group metals and sophisticated and thus expensive ligands. 64 Furthermore, especially for use with humans, strict limits for the contamination of chemicals with heavy metals apply, which are in the 1-10 ppm range.…”
Section: Scheme 12 Suzuki Coupling Of Cyclobutyltrifluoroboratesmentioning
confidence: 99%
“…[5][6][7][8][9][10] However, the high cost and residual of Pd (>25ppm after removing residual palladium by adsorption and crystallization), may not meet the demand for heavy metals content in the first-generation synthesis of axitinib, which demand for below 10ppm. 11,12 For the commercial route, a recrystallization was employed to ensure Pd levels were below 10 ppm and the formation of the desired solid form (Form XLI).…”
Section: Scheme 2 the Second-generation Synthesis Routementioning
confidence: 99%
“…However, thiol groups are susceptible to oxygen-converting thiols into disulfides via oxidative coupling [44]. iocarbonyl moieties such as thioamide [26][27][28][29][30][47][48][49][50][51][52][53], thiourethane [31,33,35,37], and thiourea [11,25,[54][55][56][57][58][59][60] have also been examined as stable adsorbents. We also have found that a polymer bearing N,N-dialkylthiourethane moieties has high adsorption ability to Pd and Au, but the adsorption from aqueous solutions only proceeded in the presence of organic solvents such as chloroform due to the hydrophobic nature of the backbone [35].…”
Section: Introductionmentioning
confidence: 99%